2017
DOI: 10.5194/acp-17-4093-2017
|View full text |Cite
|
Sign up to set email alerts
|

Wave modulation of the extratropical tropopause inversion layer

Abstract: Abstract. This study aims to quantify how much of the observed strength and variability in the zonal-mean extratropical tropopause inversion layer (TIL) comes from the modulation of the temperature field and its gradients around the tropopause by planetary-and synoptic-scale waves. By analyzing high-resolution observations, it also puts other TIL enhancing mechanisms into context.Using gridded Global Positioning System radio occultation (GPS-RO) temperature profiles from the COSMIC mission (2007-2013), we are … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 34 publications
(79 reference statements)
1
7
0
Order By: Relevance
“…The presence of high clouds supports the hypothesised importance of moist dynamical and radiative processes during the formation of the TIL (e.g. Randel et al, 2007;Kunkel et al, 2016). The composites further reveal a maximum in vertical shear of the horizontal wind S 2 within the region of strongest enhancement of static stability above the tropopause.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The presence of high clouds supports the hypothesised importance of moist dynamical and radiative processes during the formation of the TIL (e.g. Randel et al, 2007;Kunkel et al, 2016). The composites further reveal a maximum in vertical shear of the horizontal wind S 2 within the region of strongest enhancement of static stability above the tropopause.…”
Section: Discussionsupporting
confidence: 73%
“…Aside from adiabatic dynamics, diabatic processes have been shown to be of importance for the TIL. Randel et al (2007) showed that the radiative forcing of ozone and water vapour in the UTLS leads to a sharpening of the tropopause due to heating above and cooling below. Kunkel et al (2016) extended the adiabatic simulations of baroclinic waves by including the contributions from different diabatic forcings.…”
Section: Introductionmentioning
confidence: 99%
“…The tropopause inversion layer (TIL) was first discovered by Birner et al (2002) in the analysis of high vertical resolution radiosonde observations at two midlatitude stations and then proven to be a global phenomenon (Birner, 2006;Gettelman & Wang, 2015;Grise et al, 2010;Pilch Kedzierski et al, 2015Son et al, 2011). Several studies have pointed out that the TIL has close relationship with atmospheric waves (Birner, 2006;Grise et al, 2010;Kunkel et al, 2014;Miyazaki et al, 2010;Pilch Kedzierski et al, 2016, 2017Sjoberg & Birner, 2014;Wang et al, 2016;Zhang et al, 2015) and even has impacts on the vertical wave propagation (Birner, 2006;Sjoberg & Birner, 2014;Zhang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Williams and Colucci (2010) showed that RWP properties in the upper troposphere depended on lower-stratospheric conditions, namely the strength of the polar vortex. New case studies about extreme cyclones are pointing to a significant role of stratospheric conditions in their development (Odell et al, 2013;Tao et al, 2017a, b), and a more general study about severe European windstorms found that in 20 of 60 cases the stratospheric contribution during their deepening phases was over 10 % (Pirret et al, 2017). Nevertheless, despite their interaction with the stratosphere, it is generally assumed that RWPs cannot propagate upward due to the typical wind regimes in the stratosphere (Charney and Drazin, 1961).…”
Section: R Pilchmentioning
confidence: 99%